Characterization of Neurochemical Signature Alterations in the Enteric Nervous System in Autoimmune Encephalomyelitis - Kicherer, Julia; Weier, Alicia; Enders, Michael; Neuhuber, Winfried; Heider, Thorsten; Kürten, Stefanie (Applied Sciences, 2022)
To date, it has remained unclear whether gastrointestinal symptoms, which are frequently observed in patients with multiple sclerosis (MS), are accompanied by pathology of the enteric nervous system (ENS). Here, the neurotransmitter signature of ENS neurons and morphological alterations of interstitial cells of Cajal (ICCs) were studied in patients with MS and mice with experimental autoimmune encephalomyelitis (EAE), which is an animal model of MS. Immunohistochemical analysis was performed on colonic whole mounts from mice with EAE and on paraffin-embedded sections of intestinal tissue from patients with MS. Antibodies against neurotransmitters or their enzymes (including vasoactive intestinal peptide (VIP), neuronal nitric oxide synthase (nNOS), and choline acetyltransferase (ChAT)) were used in conjunction with pan-neuronal markers. In addition, the presence of anoctamin 1 (ANO1)-expressing ICCs was studied. ENS changes were observed in the myenteric plexus, but they were absent in the submucosal plexus of both EAE mice and patients with MS. There was a significant decrease in the percentage of ChAT-positive neurons in EAE mice as opposed to a trend toward an increase in patients with MS. Moreover, while ANO1 expression was decreased in EAE mice, patients with MS displayed a significant increase. Although additional studies are necessary to accomplish an in-depth characterization of ENS alterations in MS, our results imply that such alterations exist and may reveal novel insights into the pathophysiology of MS.
CRIS-Team WoS Importer:2022-07-08